Prostitution Practices Through the Disguise of a Dimly Lit Café (A Case Study of Pesaguan Village, Pangkalan Lesung District, Pelalawan Regency) - Santosa, Agung; Ramailis, Neri Widya (Sisi Lain Realita, 2024)
Prostitution is a sexual act occurring outside of marriage that has existed since ancient times and represents a complex issue intersecting social, legal, and traditional domains. In Indonesia, prostitution is considered a moral and legal violation, as well as a social deviation involving the exchange of bodily services for sexual gratification in return for payment. This practice adversely affects not only the individuals involved and their clients but also the broader community, and is difficult to eradicate due to its association with a lack of religious understanding. This study aims to explore the dynamics and factors influencing prostitution in the area and its impacts. A qualitative method is employed, utilizing data collection techniques such as observation, interviews, and documentation, involving informants including female entertainers working in clandestine bars and their patrons. The findings reveal that these clandestine bars serve as venues for prostitution, with female entertainers participating primarily due to economic reasons and unfavorable conditions. This practice has a widespread impact on the community, highlighting the need for comprehensive interventions such as enhanced religious understanding, economic empowerment, and more effective law enforcement to address the issue of prostitution.